Integrating ecological and community science data to understand patterns of colour polymorphism and social behaviour at the northern range limit of a plethodontid salamander - Alexia McCormick; Julia L. Riley (PLoS ONE, 2025)
Traditionally, scientists have relied on ecological surveys to gain information about wildlife; however, community-science data has recently emerged as a valuable resource in organismal research. In this study, we conducted ecological surveys in 23 forests in New Brunswick, Canada and extracted data from iNaturalist across the entire province to understand patterns of Eastern Red-backed Salamanders' colouration and sociality at the northern limit of its range. Ecological data revealed that adult salamanders were more likely to aggregate during the early spring and autumn, reflecting trends observed in other areas of their range. We also compared aggregation behaviour and colouration data between data collection methodologies and found that community-scientists are less likely to report aggregated salamanders and are more likely to report unique colour morphs than ecological surveys. Notably, iNaturalist observations included an amelanistic morph which had yet to be formally documented in New Brunswick. Lastly, we used our ecological survey data to explore if preferences for micro-environmental factors differ between colour polymorphism and aggregated vs. solitary salamanders. There was no evidence for environmental preferences in New Brunswick, which differs from tendencies observed in other populations of this species. Our findings highlight the trade-offs between ecological and community-science approaches and contribute valuable insights into the natural history of P. cinereus at the northern edge of its Canadian range.